(untitled) (Research, Society and Development, 2021)
The immunopathological mechanisms involved in the development of leprosy neural injury are not yet fully understood. Thus, the objective of this study was to perform an integrative review in order to identify the involvement of neurotrophin NGF and cytokine TNFα in the pathogenesis of neural injury in leprosy reactions. This review was carried out by search for scientific articles in the databases PubMed, SciELO and Google Acadêmico following the Descriptors of Health Science (DeCS) “Leprosy Reaction”, “Nerve Growth Factor (NGF)”, “Tumor Necrosis Factor- alpha (TNFα)”, and 28 articles was selected. The results showed that in the type 1 reaction there is tissue expression of IL-2, IFNg, TNFα, IL-12 and IL-1b. Whereas the type 2 or ENH reaction has been associated with high TNFα concentrations, neutrophilic infiltration and activation of complement system. High levels of NGF were observed in the lepromatous form of the disease and, low levels, in the tuberculoid form, since this stimulates the expression of TNFα, contributing to the evolution of neural lesions. There seems to be an interaction between NGF and TNFα, since NGF induces endogenous expression of TNFα and this positive feedback promotes a survival of healthy neural cells.